The Effect of Relaxation Techniques and Distraction Techniques on Reducing Pain Scale in Postoperative Patients at UKI Hospital East Jakarta in 2020 - rohyani, dwi; Helen, Millya (JOURNAL EDUCATIONAL OF NURSING(JEN), 2021)
The purpose of this study was to determine the effect of relaxation techniques and distraction techniques on reducing pain scale in postoperative patients at UKI Hospital in 2020. This study used a cross sectional study approach which aims to determine the effect of relaxation and distraction techniques on postoperative patients at UKI Hospital. Cross sectional is a method for approaching respondents (point time approach) which is carried out at one time. the independent variable is relaxation technique and the dependent variable distraction is the decrease in pain scale in postoperative patients. The results of the study concluded that there were differences in the results of the pain scale between the pre-test and post-test with the Relaxation technique in postoperative patients. Most of the respondents had moderate pain scale results as many as 77% of postoperative patients, the group after intervention with Relaxation showed that most respondents had mild pain scale results as many as 86% of postoperative patients. There is a difference in the results of the pain scale between the pre-test and post-test with the Distraction technique in postoperative patients. Most of the respondents had controlled severe pain scale results as many as 88% of patients, the group after the distraction intervention showed that most of the respondents had moderate pain scale results as many as 79% of patients.